PEMBERDAYAAN KETERAMPILAN METAKOGNITIF MELALUI PEMBELAJARAN REFLEKTIF - Deny Setiawan (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2016)
Thinking skills already begun to be applied and developed to improvestudents ready to compete in the 21st Century. One of thinking skills needed to be developed are metacognitive skills. Empowerment metacognitive skills can be done by reflective learning. Reflective learning activities that could accommodate the concept, reflection, and the questionsare learning journals. The aims of this study is to 1) determine metacognitive skills through the application of learning journals, and 2) to analyze students needs through the reflective learning journal to empower metacognitive skills. The study of this experimental research is the one shot case study design. The study population was all students of Biology. Samples are 23 General Biology course students at odd semester of 2014/2015. Data was obtained by observation, analysis learning journal and rubric asessment of metacognitive skills. The data has been analyzed through descriptive analysis. The results showed that the classical metacognitive skills score is 78,18.Learning journal is a tool that can be used to empower metacognitive skills.